REINFORCEMENT OF CONCRETE COMPOSITION BASED ON LOCAL WASTE - Abobakirova Zebuniso Asrorovna (Journals Park Publishing, 2024)
In this article, one of the priority tasks of building materials is the modernization of production technologies in the production of concrete and reinforced concrete structures using local waste without reducing their strength, improving the quality of products, as well as increasing its strength.
Keywords: Concrete, corrosion, moisture, polymer additive, Poly-ANS, minerals, superplasticizer.